2017
DOI: 10.1371/journal.pone.0169801
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Online Surveillance as a Supplementary Tool to Sentinel Doctors for Influenza-Like Illness Surveillance in Italy

Abstract: The monitoring of seasonal influenza yearly epidemics remains one of the main activity of national syndromic surveillance systems. The development of internet-based surveillance tools has brought an innovative approach to seasonal influenza surveillance by directly involving self-selected volunteers among the general population reporting their health status on a weekly basis throughout the flu season. In this paper, we explore how Influweb, an internet-based monitoring system for influenza surveillance, deploy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 14 publications
0
36
0
1
Order By: Relevance
“…InfluNet is a network of sentinel practitioners, representative of all Italian regions, based on the voluntary participation of an average 973 general practitioners and family pediatricians per year (range 754-1,055), providing health care to about 2% of the general population. InfluNet is dedicated to monitoring ILI incidence from week 42 to week 17 of each season, to defining the extent of the seasonal epidemics, and to collecting information on circulating strains (Perrotta et al, 2017;Gasparini et al, 2013).…”
Section: Influenza Activitymentioning
confidence: 99%
“…InfluNet is a network of sentinel practitioners, representative of all Italian regions, based on the voluntary participation of an average 973 general practitioners and family pediatricians per year (range 754-1,055), providing health care to about 2% of the general population. InfluNet is dedicated to monitoring ILI incidence from week 42 to week 17 of each season, to defining the extent of the seasonal epidemics, and to collecting information on circulating strains (Perrotta et al, 2017;Gasparini et al, 2013).…”
Section: Influenza Activitymentioning
confidence: 99%
“…Influweb is a scientific project aimed at monitoring the activity of Influenza-like Illness in Italy with the aid of volunteers via the internet [49,50]. It has been operational since 2008 and it is part of the InfluenzaNet network, active in many other European and non-European countries [61,62], such as The Netherlands, Belgium, Portugal, United Kingdom, Sweden, France, Spain, Denmark and Ireland.…”
Section: Influweb Datasetmentioning
confidence: 99%
“…In this work, we combine health and behavioral data, collected from Web users, with a machine learning pipeline to characterize self-initiated behavioral changes during the seasonal flu. In particular, we developed and deployed a questionnaire via Influweb [49,50], a digital surveillance platform that since 2008 collects data about the progression of the seasonal flu in Italy, to collect socio-demographic indicators, medical history of individuals, information regarding feelings, concerns towards the flu and to query users about changes in their behaviors induced by the disease. By studying the responses, we identify three classes of behavioral changes describing those that report i) no (26%), ii) only moderately (36%), iii) significant (38%) changes in behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…The list of proposed symptoms has been chosen to 45 include the various ILI definitions adopted by national surveillance systems in Europe 46 and, at the same time, to get a comprehensive list of symptoms that could be clearly 47 articulated and understood by participants and would allow the detection of various 48 circulating flu-related illnesses. Even though participatory systems generally suffer from 49 self-selection bias, causing the sample to be non-representative of the general 50 population [25], previous works have shown that web-based surveillance data can 51 provide relevant information to estimate age-specific influenza attack rates [26,27], 52 influenza vaccine effectiveness [28], risk factors for ILI [29,30], and to assess health care 53 seeking behavior [31]. Moreover, it has been largely demonstrated that weekly ILI 54 incidence rates that can be extracted from web-based surveillance data correlate well 55 with ILI incidence as reported by GPs surveillance [27,32,33] (in such approaches, the 56 number of ILI cases among the web platform participants was determined by applying 57 the ECDC case definition [13] to the set of symptoms reported by participants).…”
Section: Plosmentioning
confidence: 99%
“…24 Nevertheless, a significant fraction of European countries still adopts their own clinical 25 case definition to compile seasonal influenza surveillance weekly reports. 26 In recent years the availability of novel data streams has given rise to a variety of 27 non-traditional approaches for monitoring seasonal influenza epidemics [14][15][16]. Such 28 new digital data sources can be exploited to capture additional surveillance signals that 29 can be used to complement GPs surveillance data [17][18][19][20].…”
mentioning
confidence: 99%